CULTURE SHOCK AND CAMPUS PROGRAM IN ELT FOR THAI UNDERGRADUATE STUDENTS AT UNIVERSITY OF ISLAM SULTAN AGUNG AND UNIVERSITY OF AHMAD DAHLAN - Didik Murwantono; Rinawati Rinawati (English Review: Journal of English Education, 2021)
The existence of culture shock is undeniably true for foreign students studying in other countries. This phenomenon becomes more common nowadays. It also happened with some Thai students who are studying at University of Islam Sultan Agung Semarang and University of Ahmad Dahlan Yogyakarta. The main objectives of this article are to find out the cultural transition and to analyze the influence of culture shock and campus programs in ELT for Thai Students. This research was under a mix-method combined between qualitative and quantitative research by using purposive sampling. Twentyfour (N=24) Thai university students participated in the study. The analysis technique applied an exploratory mixed-method research design by separating the result both quantitative and qualitative. The online interview along with questionnaires was used to collect information from the students by using zoom and Google form. Data collection was performed from October to December 2020. Based on the questionnaire and interview as the primary data collection, this mini research reveals two findings. Firstly, shock culture and campus programs have a great contribution to the cultural transition in ELT. Secondly, the Thai students coped with the shock by adapting their experiences in academic programs and campus traditions. Campus programs also played a critical role in lessening culture shock.